2021
DOI: 10.1038/s41598-021-92959-6
|View full text |Cite
|
Sign up to set email alerts
|

Glutamine supplementation stimulates cell proliferation in skeletal muscle and cultivated myogenic cells of low birth weight piglets

Abstract: Muscle growth of low birth weight (LBW) piglets may be improved with adapted nutrition. This study elucidated effects of glutamine (Gln) supplementation on the cellular muscle development of LBW and normal birth weight (NBW) piglets. Male piglets (n = 144) were either supplemented with 1 g Gln/kg body weight or an isonitrogeneous amount of alanine (Ala) between postnatal day 1 and 12 (dpn). Twelve piglets per group were slaughtered at 5, 12 and 26 dpn, one hour after injection with Bromodeoxyuridine (BrdU, 12 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…We have previously shown that the supplementation of Gln from age day 1 to 12 increased growth and milk intake in LBW piglets which was associated to changes in lipid metabolism suggesting Gln effects on the splanchnic tissue [ 31 ]. Additionally, in a companion paper we reported that Gln supplementation resulted in Gln accumulation in skeletal muscle of 5-day old piglets and that Gln supplementation was associated with larger muscle fibers [ 42 ], as well as higher cellular proliferation in skeletal muscle [ 43 ]. Collectively, these results appear to support earlier findings on the growth-promoting effect of glutamine in pre-weaning piglets [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that the supplementation of Gln from age day 1 to 12 increased growth and milk intake in LBW piglets which was associated to changes in lipid metabolism suggesting Gln effects on the splanchnic tissue [ 31 ]. Additionally, in a companion paper we reported that Gln supplementation resulted in Gln accumulation in skeletal muscle of 5-day old piglets and that Gln supplementation was associated with larger muscle fibers [ 42 ], as well as higher cellular proliferation in skeletal muscle [ 43 ]. Collectively, these results appear to support earlier findings on the growth-promoting effect of glutamine in pre-weaning piglets [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…While isotopomer labeling patterns are indicative of the enzymatic changes that would facilitate changes in intermediate use, the complex interplay between the regulation of enzyme expression and activity increases the burden of elucidating these molecular mechanisms. Ultimately, it is clear that glutamine and glutamate supplementation facilitates protein synthesis [38][39][40], but further investigation to understand the intricacies of amino acid utilization during postnatal growth is necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Amino acids and proteins are required for cell growth. The effects of glutamine and leucine on cell proliferation and EV biogenesis have been documented (Dai et al., 2015 ; Fan et al., 2020 ; Kim et al., 2017 ; Rubin, 2019 ; Zhao et al., 2021 ). If stabilized versions of amino acids are used as supplements, a different concentration of this amino acid in the medium over time will be maintained than when using the native version.…”
Section: Ev Production Mediummentioning
confidence: 99%